Girls' Education and Child Marriage in West and Central Africa : Trends, Impacts, Costs, and Solutions - Male, Chata; Wodon, Quentin (Taylor and Francis, 2018)
Within the context of women’s lack of empowerment, the issues of child marriage and low educational attainment for girls are prominent, especially in West and Central Africa. Using survey data for 21 of the 25 countries in West and Central Africa, this article analyzes trends over time in educational attainment for girls and child marriage. Over the last two and a half decades, not accounting for differences in population sizes between countries, according to the latest DHS and MICS surveys available in each country, completion rates increased on average by 24 points, 14 points, and 8 points at the primary, lower secondary, and upper secondary levels, respectively. The prevalence of child marriage decreased by about 8 points over that period. Clearly, progress at the secondary level has been weaker than at the primary level, probably in part due to the persistence of high rates of child marriage in many countries. The article suggests that ending child marriage should improve girls’ educational attainment, and conversely, improving girls’ educational attainment should help reduce child marriage. This, in turn, could have major impacts toward contributing to empowering women more broadly. A review of impact evaluations for pilot interventions suggests how ending child marriage and improving educational attainment for girls could be done, with potentially large economic benefits not only for girls and their future household, but also for the region as a whole.